Diverse Functions of γδ T Cells in the Progression of Hepatitis B Virus and Hepatitis C Virus Infection - Hou, Wen; Wu, Xiaoli (Frontiers in Immunology, 2021)
Hepatitis B virus (HBV) and hepatitis C virus (HCV) infections are primary risk factors for a wide spectrum of liver diseases that severely affect human health. The liver is an immunological organ that has an abundance of immune cells. Thus, various innate or adaptive immune cells are involved in the progression of HBV or HCV infection. Among those cells, a unique kind of immune cell, the γδ T cell, contributes to promoting or inhibiting the progression of liver diseases. To reveal the diverse roles of γδ T cells in HBV or HCV infection, the properties and functions of these cells in human and mouse models are analyzed. Here, we briefly describe the characteristics and functions of γδ T cells subsets in liver diseases. Then, we fully discuss the diverse roles of γδ T cells in the progression of HBV or HCV infection, including stages of acute infection, chronic infection, liver cirrhosis, and hepatocellular carcinoma. Finally, the functions and existing problems of γδ T cells in HBV or HCV infection are summarized. A better understanding of the function of γδ T cells during the progression of HBV and HCV infection will be helpful for the treatment of virus infection.